2012
DOI: 10.1055/s-0032-1316318
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Nitric Oxide and Alpha-Amylase as Indexes of Training Intensity and Load

Abstract: This study examined the variation in salivary nitric oxide (NO), alpha-amylase (sAA) and serum markers of muscle injury during 21 weeks of training in elite swimmers. Samples of saliva and blood were collected once a month during 5 months from 11 male professional athletes during their regular training season. The variation in each marker throughout the 21 weeks was compared with the dynamics of training volume, intensity and load. Unstimulated whole saliva was assessed for NO and sAA whereas venous blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 26 publications
(30 reference statements)
2
43
2
3
Order By: Relevance
“…49 In another study, it has been indicated that the concentration of NO increased throughout about 5 months of training in elite swimmers (mean aged: 21.5 years). 48 Similar variations were also observed in the salivary NO concentration and muscle injury markers such as CK. Salivary NO levels showed a proportional response to oscillations in training intensity and load.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…49 In another study, it has been indicated that the concentration of NO increased throughout about 5 months of training in elite swimmers (mean aged: 21.5 years). 48 Similar variations were also observed in the salivary NO concentration and muscle injury markers such as CK. Salivary NO levels showed a proportional response to oscillations in training intensity and load.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that both acute and regular aerobic exercise in swimmers and sedentary group increase blood NOx levels. 23,47,48 The best-established stimulus of NO production is shear stress, which increases during increased blood flow and can increase NOS activity. Furthermore, it has been reported that all isoforms of NOS can be regulated by transcription with hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Some biochemical components of saliva have highly specific bands in the infrared region, including those considered important biomarkers to evaluate physical stress (Diaz et al, 2013;Khaustova et al, 2009;Moreira et al, 2013). Khaustova et al (2010) showed that the regions 1503-1440 cm -1 to levels of α-amylase.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated great possibilities of saliva to monitor bodily changes, such as metabolic disorders (Gonnissen et al, 2012), anemia (Jagannathan et al, 2012), DNA markers (Omelia et al, 2013), doping control (Thieme, 2012), and especially the physiological changes in athletes resulting from exercise training (Diaz et al, 2013;Moreira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation